Multipoint measurements of a Pipe Using HTS-SQUID and Magnetostriction-Based Ultrasonic Guided Wave. (September 2019) - Azuma, Y; Terawaka, T; Kubota, S; Yokouchi, Y; Hatsukade, Y; Adachi, S; Tanabe, K
Abstract: This paper describes study on remote inspection technology for pipes by using magnetostriction-based ultrasonic guided wave and high temperature superconductor (HTS) superconducting quantum interference device (SQUID) gradiometer. Magnetized nickel plates were adhered on an aluminium pipe sample, in order to use them as magnetostriction-based guided wave transceivers. A pair of 10mm-wide nickel plate with different angle arrangement were used to transceive uniformly distributed guided waves at all angles. A field coil was wound around one set of the nickel plates as a transmitter, while the other was used as a receiver. T (0, 1) mode guided wave was generated on the pipe by supplying a burst sine wave current of one cycle at several tens kHz to the coil. Multipoint measurements of the T (0, 1) mode guided waves around the pipe's circumference were carried out by setting the HTS-SQUID gradiometer above the receiver with lift-off of about 9 mm and rotating the pipe for 360 degrees. Signal of reflected wave from an artificial slit on the sample was well detected. We simulated the distribution of the guided wave propagating on the pipe with the slit using an ultrasonic simulator and compared the distribution with the experiment result. The guided wave signal distributions including the defect signal obtained by experiment and simulation agreed well.